Respon Pertumbuhan Dan Hasil Jagung Lokal (Zea Mays L.) Varietas Talango Terhadap Pemberian Selenium (Se) - Ahmad Faried Ardiansah; Denna Eriani Munandar (Jember University Press, 2022)
Local maize plants have prospects to be developed in line with the increasing demand and level of community consumption. One of the local varieties of maize, the Talango variety, has the advantages of early maturity of 75 days, long shelf life, high yield of maize and cheap seed prices. The nutritional content of the Talango variety is higher than that of hybrid maize, such as 11.24% protein, 4.96% fat and 75.6% carbohydrates. This study were to determine the best dose of selenium to growth and yield of local maize (Zea mays L.) Talango varieties. This study used Randomized Block Design (RBD) one factor consisting A0 = 0 µm, A1 = 5 µm, A2 = 10 µm, A3 = 15 µm, A4 = 20 µm, A5 = 25 µm, A6 = 30 µm, A7 = 35 µm, A8 = 40 µm, A9 = 45 µm. Each treatment will be repeated 4 times so that there are total 40 experimental units. The research variebles included plant height, root wet weight, shoot wet weight, total wet weight, flowering age, seed weight and 100 seed weight. The data obtained will be analyzed using analysis of variance (ANOVA). The result will be analyzed using Duncan Multiple Range Test (DMRT) level of α 5% to compare the effect between treatments on plant yield. The treatment of selenium (Se) doses at different levels had a positive effect on increasing the observed variables of root fresh weight, shoot fresh weight, total fresh weight, flowering age, seed weight per plant and 100 seed plant weights. The results showed that the Se treatment with doses of 20 μM to 25 μM and 35 μM to 40 μM produced the best seed weight per plant in the range of 59.25 g – 79.84 g which was significantly different from the control and other treatment doses. Keywords: Local maize, Talango varieties, Selenium